Non-traditional international assignments, knowledge and innovation: an exploratory study of women's experiences. (1st September 2015) - Miralles-Vazquez, Laia; McGaughey, Sara L.
Abstract : For many multinational corporations (MNCs), sustainable competitive advantage resides in an MNC's ability to innovate; that is, to create new knowledge, integrate it with an existing knowledge base and exploit the resulting knowledge bundles across national borders. Traditionally, a key mechanism by which knowledge is transferred across borders and recombined works through expatriate assignments. There is, however, a growing trend towards alternative forms of international assignments, such as flexpatriates, commuters, frequent flyers and self-initiated expatriates. We ask how the use of such non-traditional international assignments affects knowledge creation and transfer in MNCs and hence innovation, which we construe as both idea generation and implementation. Our exploratory study draws on the experiences of five women living in Spain who undertook various forms of international assignment in MNCs with differing administrative heritages, working in consultancy and engineering fields. Our findings point to variations in the type and quality of knowledge generated across different forms of international assignments, and draw attention to the socially embedded, informal interactions underpinning much knowledge transfer and recombination. Our findings are also suggestive of a gendered element to knowledge creation and transfer, and how these activities may be perceived by the senior management of MNCs. Our concluding conjecture is that within each form of international assignment, women's contributions to the innovative efforts of MNCs may have somewhat less to do with formal management practices, and may even, at times, be in spite of them.